Problem-oriented policing, deterrence, and youth violence: an evaluation of Boston's operation ceasefire - Braga, Anthony Allan; Kennedy, David M.; Waring, Elin J.; Piehl, Anne Morrison (Journal of research in crime and delinquency, 2001)
Operation Ceasefire is a problem-oriented policing intervention aimed at reducing youth homicide and youth firearms violence in Boston. It represented an innovative partnership between researchers and practitioners to assess the city's youth homicide problem and implement an intervention designed to have a substantial near-term impact on the problem. Operation Ceasefire was based on the "pulling levers" deterrence strategy that focused criminal justice attention on a small number of chronically offending gang-involved youth responsible for much of Boston's youth homicide problem. Our impact evaluation suggests that the Ceasefire intervention was associated with significant reductions in youth homicide victimization, shots-fired calls for service, and gun assault incidents in Boston. A comparative analysis of youth homicide trends in Boston relative to youth homicide trends in other major U.S. and New England cities also supports a unique program effect associated with the Ceasefire intervention